2005
DOI: 10.1590/s0036-46652005000200005
|View full text |Cite
|
Sign up to set email alerts
|

Melanoides tuberculatus (Gastropoda: Thiaridae) as intermediate host of Heterophyidae (Trematoda: Digenea) in Rio de Janeiro metropolitan area, Brazil

Abstract: In the late 1960s, Melanoides tuberculatus snails were introduced in Brazil from North/East Africa and Southeast Asia. The first records of specimens infected with cercariae were registered in Rio de Janeiro State in 2001. The present study reports the occurrence of M. tuberculatus infected with larval trematodes in Rio de Janeiro City. Bottom sediment was collected with dip nets and sieved through 0.25 inch-mesh screening. Snails were transported to the laboratory in vials with stream water, then measured and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 11 publications
1
12
0
5
Order By: Relevance
“…Rocha-Miranda and Martins- Silva (2006), in a comparative analysis of two populations in the Paraná River basin, pointed out certain differences in the structure of the populations: one being formed mostly by young individuals (belonging to the 0-0.4 cm size class) and the other composed of adult individuals (between 2.0 and 2.4 cm). However, there are records of individuals 3.3 cm (Bogéa et al, 2005) and up to 4 cm in length. M. tuberculatus can reproduce sexually, but reproduces mainly via parthenogenesis, which partly accounts for its success as an invasive organism; it is viviparous.…”
Section: Discussionmentioning
confidence: 99%
“…Rocha-Miranda and Martins- Silva (2006), in a comparative analysis of two populations in the Paraná River basin, pointed out certain differences in the structure of the populations: one being formed mostly by young individuals (belonging to the 0-0.4 cm size class) and the other composed of adult individuals (between 2.0 and 2.4 cm). However, there are records of individuals 3.3 cm (Bogéa et al, 2005) and up to 4 cm in length. M. tuberculatus can reproduce sexually, but reproduces mainly via parthenogenesis, which partly accounts for its success as an invasive organism; it is viviparous.…”
Section: Discussionmentioning
confidence: 99%
“…This snail is considered to be invasive after its introduction into new territories, and it has become established in numerous countries outside its native range (Pointier 2001;Rocha-Miranda and MartinsSilva 2006;Derraik 2008). Also, M. tuberculata has proved to be a compatible intermediate host for several trematode species of medical and veterinary importance (Dung et al 2010;Mukaratirwa et al 2004;Bogéa et al 2005;Lun et al 2005). In general, reports on snails of the group Prosobranchia serving as intermediate hosts for bird schistosomes are rare (Aldhoun et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the possible use of M. tuberculata as a biological control strategy against schistosomiasis must be considered with caution because of possible damage to the native fauna (as an alien species), and the potential of M. tuberculata to act as an intermediate host for parasites of medical and veterinary importance in Brazil are not fully understood. Some studies have already reported the finding of M. tuberculata that harbor Pleurolophocercous cercariae in Brazil 4,5,33 . Recently this cercarian type found in M. tuberculata from the state of Minas Gerais was identified as Centrocestus formosanus (Nishigori, 1924) 28 .…”
Section: Introductionmentioning
confidence: 99%